THE ROLE OF ACTIVE GAMES IN EDUCATION OF PRESCHOOL CHILDREN - Ismatov Abdukodir Isabaevich; Lapasova Gulnora; Hayitboyeva Shaxlo (Journals Park Publishing, 2022)
The article discusses the possibilities for children to find active ways to solve a game problem, creating opportunities for their game.
Keywords: game; game forms; role of the game